MYTHOLOGIZING OF BAROQUE: ARCHETYPE FORMS OF INTERPRETATION IN VALERY SHEVCHUK’S TEXT AESTHETIC STRUCTURES - Soletsky, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article describes the archetype form of interpretation in Valery Shevchuk’s text aesthetic structures and it was found that the tradition and the ways of transferring the archetypes (images, ideas, motifs and themes) were mediated by the baroque context and marked by the interpretive options which were typical for Baroque. The author believes that the reconstruction of the baroque world in the prose texts of Valery Shevchuk is created on the principles of mythologizing of narrative art.